2011
DOI: 10.1097/mpa.0b013e318201654a
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of Endoscopic Ultrasonography and Magnetic Resonance Cholangiopancreatography in the Etiological Diagnosis of "Idiopathic" Acute Pancreatitis

Abstract: Endoscopic ultrasonography and MRCP are useful techniques in the etiological diagnosis of acute pancreatitis of nonestablished cause. Endoscopic ultrasonography should be preferred for establishing a possible biliary etiology in patients who have not had a cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 37 publications
2
18
2
Order By: Relevance
“…There are three studies which has directly compared EUS and MRCP in IAP[ 18 , 43 , 44 ]. All have found higher diagnostic yield of EUS particularly to exclude biliary causes.…”
Section: What Is Idiopathic Pancreatitis?mentioning
confidence: 99%
See 2 more Smart Citations
“…There are three studies which has directly compared EUS and MRCP in IAP[ 18 , 43 , 44 ]. All have found higher diagnostic yield of EUS particularly to exclude biliary causes.…”
Section: What Is Idiopathic Pancreatitis?mentioning
confidence: 99%
“…The diagnostic yield of EUS was more than that of MRCP (51% vs 20%, P = 0.001). It was concluded that EUS should be performed for establishing a possible biliary aetiology in patients with intact gall bladder (GB)[ 44 ]. In a study of 40 patients with MRCP negative IAP by Rana et al[ 18 ], the diagnostic yield of EUS was 55%.…”
Section: What Is Idiopathic Pancreatitis?mentioning
confidence: 99%
See 1 more Smart Citation
“…Of totally 222 unique studies that were retrieved by using the key word “EUS”, 122 were excluded duing to irrelevant topics, 61 were excluded as reviews and 32 were excluded as case reports. Eventually, 7 studies met the inclusion criteria and were therefore included in meta-analysis of EUS 16 19 26 27 28 29 30 ( Fig. 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…In a prospective comparison of EUS and MRCP for etiological diagnosis of idiopathic acute pancreatitis in 49 patients, MRCP could identify PD in 4 patients, whereas EUS could diagnose PD in only 1 patient. [ 20 ] However, the low detection rate of PD by EUS may be due to operator-dependent imaging. In a large series of patients with PD, secretin-stimulated EUS (S-EUS) showed dilation of the dorsal duct by 1 mm or more following intravenous secretin.…”
Section: Introductionmentioning
confidence: 99%